The cancer‐related transcription factor RUNX2 modulates expression and secretion of the matricellular protein osteopontin in osteosarcoma cells to promote adhesion to endothelial pulmonary cells and lung metastasis. Issue 8 (13th January 2019) - Villanueva, Francisco; Araya, Hector; Briceño, Pedro; Varela, Nelson; Stevenson, Andres; Jerez, Sofia; Tempio, Fabian; Chnaiderman, Jonas; Perez, Carola; Villarroel, Milena; Concha, Emma; Khani, Farzaneh; et al.
Abstract: Osteosarcomas are bone tumors that frequently metastasize to the lung. Aberrant expression of the transcription factor, runt‐related transcription factor 2 (RUNX2), is a key pathological feature in osteosarcoma and associated with loss of p53 and miR‐34 expression. Elevated RUNX2 may transcriptionally activate genes mediating tumor progression and metastasis, including the RUNX2 target gene osteopontin ( OPN/SPP1 ). This gene encodes a secreted matricellular protein produced by osteoblasts to regulate bone matrix remodeling and tissue calcification. Here we investigated whether and how the RUNX2/OPN axis regulates lung metastasis of osteosarcoma. Importantly, RUNX2 depletion attenuates lung metastasis of osteosarcoma cells in vivo. Using next‐generation RNA‐sequencing, protein‐based assays, as well as the loss‐ and gain‐of‐function approaches in selected osteosarcoma cell lines, we show that osteopontin messenger RNA levels closely correlate with RUNX2 expression and that RUNX2 controls the levels of secreted osteopontin. Elevated osteopontin levels promote heterotypic cell–cell adhesion of osteosarcoma cells to human pulmonary microvascular endothelial cells, but not in the presence of neutralizing antibodies. Collectively, these findings indicate that the RUNX2/OPN axis regulates the ability of osteosarcoma cells to attach to pulmonary endothelial cells as a key step in metastasis of osteosarcoma cells to the lung. Abstract : In the present study, we examined the functional role of runt‐related transcription factor 2 (RUNX2) in lung metastasis. Our results indicate that RUNX2 regulates secretion of osteopontin, which promotes cell–cell adhesion between osteosarcoma cells and pulmonary endothelial cells. Thus, the RUNX2/OPN axis regulates late steps of lung metastasis by controlling the metastatic potential of osteosarcoma cells.